Pemberdayaan Masyarakat Nagari Batu Kalang Indah terkait Urgensi Hijauan Pakan Ternak - Tinda Afriani; Mangku Mundana; Adisti Rastosari; Moch. Evan Setiawan (Warta Pengabdian Andalas, 2023)
Forage is all food ingredients derived from plants, in the form of leaves, sometimes including stems, twigs, and flowers. Included are grasses, legumes and other plants. All can be fed for ruminants in two forms, i.e. fresh and dry forage. Forages contain almost all the substances animals need. The urgency of forage becomes a crucial point in increasing livestock productivity. The success of a livestock business depends on its feed management. Feed requirements of each animal vary according to the type, age, body weight, environmental conditions and physiological conditions of livestock. Community engagement was carried out with the Batu Kalang Indah cattle group. As many as 20 farmers attended the counselling activity. In addition to socialization activities, 4,000 stalks of grass were also planted, under the name King Grass, using a demonstration method for the groups. The community service activities carried out were responded to positively by the Batu Kalang Indah cattle group.